Model Kekuasaan Politik Ibnu Khaldun (Sebuah Pelajaran Berharga bagi Bangsa Indonesia) - Mansur Mansur (Universitas Islam Indonesia, 2007)
Ibnu Khaldun has been adorable for both Moslem and Western scholars because of its political thought. He has been considered as the world property, whose thought should be conserved and reproduced. This article discusses the concept of political power in accor- dance with Ibnu Khaldun thought. The discussion will be focused on political thought of him in relation to the reality of national leadership of Indonesia, which is now entering the political reform stages. Keywords: Ibnu Khaldun, political thought, national leadership, reform, Indonesia.